Genetic markers associated with power athlete status - Maciejewska-Skrendo, A.; Cieszczyk, P.; Chycki, J.; Sawczuk, J.; Smólka, W. (Journal of Human Kinetics, 2019)
Performance is a multifactorial phenotype influenced by environmental factors as well as multiple genetic variants. Different genetic elements have a great influence over components of athletic performance such as endurance, strength, power, flexibility, neuromuscular coordination, psychological traits and other features important in sport. The current literature review revealed that to date more than 69 genetic markers have been associated with power athlete status. For the purpose of the present review we have assigned all genetic markers described with reference to power athletes status to seven main groups: 1) markers associated with skeletal muscle structure and function, 2) markers involved in the inflammatory and repair reactions in skeletal muscle during and after exercise, 3) markers involved in blood pressure control, 4) markers involved in modulation of oxygen uptake, 5) markers that are regulators of energy metabolism and cellular homeostasis, 6) markers encoding factors that control gene expression by rearrangement of chromatin fibers and mRNA stability, and 7) markers modulating cellular signaling pathways. All data presented in the current review provide evidence to support the notion that human physical performance may be influenced by genetic profiles, especially in power sports. The current studies still represent only the first steps towards a better understanding of the genetic factors that influence power-related traits, so further analyses are necessary before implementation of research findings into practice.